2015
DOI: 10.1002/chin.201519260
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Flavonol Glycosides and Iridoids from Asperula lilaciflora

Abstract: A new flavonol glycoside, quercetin 3-O-[6'''-O-3,5-dihydroxycinnamoyl-b-glucopyranosyl-(1 ! 2)]-b-galactopyranoside (named lilacifloroside; 1) and a new iridoid 2 (named asperulogenin), were isolated from the aerial parts of Asperula lilaciflora in addition to eight known secondary metabolites, i.e., quercetin, kaempferol, quercetin 3-O-b-glucopyranosyl-(1 ! 2)-b-galactopyranoside, quercetin 3-O-bglucopyranosyl-(1 ! 2)-arabinopyranoside, asperuloside, deacetylasperulosidic acid, asperulosidic acid methyl este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…caucasica [12]. Other phytochemical studies have shown that Asperula species also contains iridoid glycosides (involucratosides A-C, adoxoside), flavone glycosides (apigenin 7-O-β-glucopyranoside, luteolin 7-Oβ-glucopyranoside, apigenin 7-O-rutinoside, lilacifloroside, quercetin, kaempferol, quercetin 3-O-βglucopyranosyl-(1→2)-β-galactopyranoside, quercetin 3-O-β-glucopyranosyl-(1→2)arabinopyranoside) and phenolic acid derivatives (chlorogenic acid and ferulic acid 4-O-βglucopyranoside) [13,14]. Some previous studies have shown that some Asperula species have antihypoxic and potent sedative, antioxidant activity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…caucasica [12]. Other phytochemical studies have shown that Asperula species also contains iridoid glycosides (involucratosides A-C, adoxoside), flavone glycosides (apigenin 7-O-β-glucopyranoside, luteolin 7-Oβ-glucopyranoside, apigenin 7-O-rutinoside, lilacifloroside, quercetin, kaempferol, quercetin 3-O-βglucopyranosyl-(1→2)-β-galactopyranoside, quercetin 3-O-β-glucopyranosyl-(1→2)arabinopyranoside) and phenolic acid derivatives (chlorogenic acid and ferulic acid 4-O-βglucopyranoside) [13,14]. Some previous studies have shown that some Asperula species have antihypoxic and potent sedative, antioxidant activity [15,16].…”
Section: Introductionmentioning
confidence: 99%